The immunobiology of mucosal-associated invariant T cell (MAIT) function in primary biliary cholangitis: Regulation by cholic acid-induced Interleukin-7. (June 2018) - Jiang, Xiang; Lian, Min; Li, Yanmei; Zhang, Weici; Wang, Qixia; Wei, Yiran; Zhang, Jun; Chen, Weihua; Xiao, Xiao; Miao, Qi; Bian, Zhaolian; Qiu, Dekai; et al.
Abstract: Mucosal-associated invariant T (MAIT) cells are novel innate-like T cells constituting a significant proportion of circulating and hepatic T cells. Herein, we extensively examine the phenotypical and functional alterations of MAIT cells and their regulation in a cohort of 56 patients with Primary Biliary Cholangitis (PBC) and 53 healthy controls (HC). Additionally alterations of MAIT cells were assessed before and after UDCA treatment. Finally the localization of MAIT cell in liver was examined using specific tetramer staining and the underlying mechanisms of these alterations in PBC were explored. Our data demonstrated that the frequency and number of circulating MAIT cells were decreased, whereas hepatic MAIT cells were increased in PBC compared to HC. Moreover, circulating MAIT cells were more activated in PBC than HC, reflected by elevated expression levels of granzyme B. Six months of UDCA treatment significantly attenuated the circulating MAIT cells differences in PBC. Of note, the expression levels of IL-7 were significantly increased in both plasma and liver from PBC as compared to HC, which promoted the production of inflammatory cytokines and granzyme B by inducing signal transduction and activation of transcription 5 (STAT5) phosphorylation in MAIT cells. Finally, cholic acid, one of the major bile acids in liver, upregulated IL-7 expression in hepatocyte cell line L02 by inducing Farnesoid X Receptor (FXR) binding to the IL-7 promoter. Hence MAIT cells are activated and enriched in the liver of PBC. Cholic acid-induced IL-7 production in hepatocytes plays a critical role in regulating MAIT cell function, highlighting that hepatocytes may bridge cholangiocyte injury and innate immunity through a bile acid signaling pathway. Highlights: An indispensable role of MAIT cells in PBC was suggested. MAIT cells are more activated with increased cytokine production in PBC. IL-7 enhanced cytokine production in MAIT cells in PBC. Bile acids can affect MAIT cell functions through regulating expression of IL-7.